Vapor pressure, vapor-liquid equilibria, liquid-liquid equilibria and excess enthalpy of the system consisting of isophorone, furfural, acetic acid and water. (2nd February 2018) - Ershova, Olga; Pokki, Juha-Pekka; Zaitseva, Anna; Alopaeus, Ville; Sixta, Herbert
Highlights: The phase equilibria for isophorone-furfural-water-acetic acid system were studied. LLE parameters for isophorone-furfural-water system were studied for the first time. The parameters for UNIQUAC-HOC model were optimized based on experimental results. Isophorone is found to be an efficient solvent for furfural extraction. Abstract: In this work, the phase equilibria of the system comprised of isophorone, furfural, water and acetic acid were studied from the viewpoint of the extraction process. Equilibrium vapor pressure of pure isophorone was measured at sub-atmospheric pressure. Isobaric (at 40 kPa) isophorone-furfural vapor-liquid equilibria, the excess enthalpy of isophorone-furfural mixture (at 323 K) and isophorone-acetic acid vapor-liquid equilibria (from 322 K to 342 K) were investigated and compared to the available literature data. Liquid-liquid equilibria of systems comprised of isophorone-furfural-water (from 303 K to 343 K) were measured for the first time. The experimental results of this study and the literature values were utilized for optimizing the parameters for UNIQUAC model. The model was validated against the measured liquid-liquid equilibrium of the quaternary system isophorone-furfural-acetic acid-water (from 298 K to 343 K). Isophorone was found to be a favorable solvent for furfural extraction from its aqueous solutions.